Review on electrical submersible pump failures detection and monitoring system - Sharifah Nur Fatieha Mohamad; Nurafnida Afrizal; Muhammad Zalani Daud; Md Rabiul Awal (International Journal of Advances in Applied Sciences, 2024)
An artificial lift is a technique for pumping fluids in the petroleum industry today. Most artificial lift that is used nowadays is an electrical submersible pump (ESP). ESP is very convenient and reliable for lifting production. It applies under offshore and onshore industries, where it has high displacement capacity and flexibility to handle various sizes and flow rates under different well conditions. Due to severe operating conditions, ESP may experience fatigue failure, an undesirable malfunction resulting in a shortened service life. Early failure detection on ESP is imperative to prevent a major failure in the pump and reduce the cost of the damage. This study provides an in-depth examination of condition monitoring and early failure detection, with a focus on mechanical and electrical failures. This paper begins with a description of the ESP working principle followed by an analysis of ESP fault and numerous ESP performance monitoring techniques, including the application of early detection. Finally, the authors summarize ESP’s failures, including detection methods for each failure. Besides, recommendations for future research to increase ESP’s lifetime are also discussed. This review revealed that the lifetime of existing ESP can be extended if extensive monitoring of ESP conditions and advanced fault detection methods are applied.